ETHICS OF CONSUMPTION AND MUSLIM CONSUMER BEHAVIOR IN AN ERA OF ECONOMIC UNCERTAINTY - Dhina Wahyuni; Abdul Azis; Abdul Husenudin; Nida Hamidah; Nendys Rismala Haliza Malik; Muhammad Randi; Audia Klarisa Pascalia; Lara Nada Bakri (STMIK Indonesia Banda Aceh, 2026)
This research aims to analyze the ethics of consumption and the behavior of Muslim consumers in an era of economic uncertainty. Unstable economic conditions, characterized by price and income fluctuations, encourage consumers to be more selective, rational, and cautious in making consumption decisions. The research uses a qualitative literature method by analyzing various literary sources related to Muslim consumption behavior, Islamic ethical principles, and consumer adaptation to economic dynamics. The results show that Muslim consumer behavior is influenced by economic factors, trust, technology, and religious values. Although economic pressures can affect consumption priorities, Islamic consumption ethics still act as a control mechanism, promoting principles of moderation, simplicity, and social care. This research contributes to understanding the dynamics of adaptive, balanced, and sharia-compliant Muslim consumer behavior amidst economic uncertainty.